2011
DOI: 10.1007/s10096-011-1229-7
|View full text |Cite
|
Sign up to set email alerts
|

A prospective survey of Aspergillus spp. in respiratory tract samples: prevalence, clinical impact and antifungal susceptibility

Abstract: A three-month laboratory-based prospective survey was conducted at four major university hospitals covering one-third of the Danish population in order to determine the prevalence, significance, and susceptibility pattern of aspergilli in airway samples. Samples received in January-March 2007 for routine microbiologic investigation were examined for Aspergillus following routine procedures and with extended incubation (5 days). Identification was done by morphologic criteria and susceptibility testing using EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
63
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 50 publications
4
63
1
2
Order By: Relevance
“…However, in the majority of CF patients, isolation of Aspergillus spp. only confirms colonization and/or diagnosis of allergic bronchopulmonary aspergillosis (6−25%) [20]. The Danish research showed 65.5% of colonization cases of the lower airways with Aspergillus spp.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, in the majority of CF patients, isolation of Aspergillus spp. only confirms colonization and/or diagnosis of allergic bronchopulmonary aspergillosis (6−25%) [20]. The Danish research showed 65.5% of colonization cases of the lower airways with Aspergillus spp.…”
Section: Discussionmentioning
confidence: 97%
“…The literature reports rare cases of invasive aspergillosis in people with CF. Mortensen et al presented two cases of invasive fungal infection of A. fumigatus etiology [20]. However, in the majority of CF patients, isolation of Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations